Peningkatan Kesadaran akan Kesehatan Mental dalam Mengatasi Beban Akademik pada Siswa Kelas 9 SMP Islam Tirtayasa - Kusumaningsih, Rila (Dharma: Jurnal Pengabdian Masyarakat, 2024)
Mental health disorders are a form of dysfunction and disturbance in mental functions caused by the failure of adaptive mechanisms to respond to external stimuli and tensions, resulting in disorders in mental structure. Mental health disorders represent the totality of pathological mental expressions toward social stimuli, combined with other secondary factors. Mental health disorders in adolescent students in a school environment can be caused by various factors, such as bullying, family disharmony, academic burdens such as difficulty understanding a subject, parental pressure to achieve certain grades, and the emphasis on the need to perform as well as siblings. This Community Engagement activity was conducted in September 2022 in three stages: preparation, implementation, and evaluation. This service activity aims to provide an understanding of the importance of mental health among teenagers, especially in overcoming academic burdens. Mental health disorders were found among a random sample of 9th-grade students, with the majority experiencing mental health disorders due to academic burdens. There is a strong correlation between the mental health disorders they experience and academic burdens. Therefore, it is necessary to pay more attention to the mental health of 9th-grade students at Tirtayasa Islamic Junior High School.